A compact size microstrip five poles hairpin band-pass filter using three-layers structure for Ku-band satellites application - Qazwan, Abdullah; Nor Shahida, Mohd Shah; Nabil, Farah; Jabbar, Waheb A.; Noorsaliza, Abdullah; Salh, Adeeb; Mukred, Jameel A. A. (Universitas Ahmad Dahlan, 2020)
This paper presents a reduced size microstrip five poles hairpin band-pass filter using three-layers structure for Ku-band satellites application. The three-layers structure shows a substantially reduced filter size and enlarged bandwidth. The filter has been designed based on five-pole resonators at 12.475 GHz and bandwidth of 550 MHz. This filter is designed on Rogers RO3003 substrate having relative permittivity (εr) of 3. The proposed band-pass filter has been designed with the help of Computer Simulation Technology (CST) software. Comparison analyses between the simulated insertion loss and reflection coefficient of RO3003 and FR4 substrates have been carried out in order to show the efficiency of the proposed filter design. Based on the obtained results, the proposed filter design achieves significant filter size reduction compared to other band-pass filters.